Monetary policies and independence of the central banks in E7 countries - Dinçer, Hasan; Yüksel, Serhat (IGI Global, 2019)
Central banking independence is a crucial factor for sustainable economic development of multiple countries. The multiple components for such systems, however, makes it difficult to evaluate how the success of such a system may be determined. Monetary Policies and Independence of the Central Banks in E7 Countries is an essential reference source that evaluates the effectiveness of monetary policies and the independence of central banks to contribute to economic development within seven emerging economies (E7): Brazil, China, India, Indonesia, Mexico, Russia, and Turkey. Featuring research on topics such as global economics, independent banking, and foreign investing, this book is ideally designed for financial analysts, economists, government officials, policymakers, researchers, academicians, industry professionals, and students seeking coverage on improved econometric methods for effective financial systems.
Keywords: E7 Countries; Central Banks; Monetary Policies